Capacity to Mediate and the Human Right to Self Determination: The Mediator’s Responsibility! - Condell, Mary (Journal of Mediation and Applied Conflict Analysis, 2015)
The purpose of this paper is to examine capacity in a mediation context including the level of responsibility a mediator has for assessing the capacity of participants; when that assessment should be made; and whether or not there are any guiding principles available to assist mediators in making the assessment. This is carried out, by reference to the available literature, under the following headings: the human rights origins of self-determination; capacity in a mediation context; the internationally recognised approaches to capacity; the best approach to capacity for mediators; and the obligations which will be imposed on mediators working in Ireland in view of the imminent Assisted Decision Making (Capacity) Bill 2013. The paper additionally looks at the skills necessary to assess capacity in mediation and asks if mediators’ training adequately provides them, and concludes that the responsibility to assess capacity to mediate rests solely with the mediator.